Classroom Assessment in Enhancing Learning Achievement in English: A Phenomenological Study - Kadel, Purna Bahadur (Education Review Journal, 2024)
This article is an attempt to address the perceptions of English teachers on the roles of cognitive domains of Bloom Taxonomy in enhancing the learning achievement of learners at the secondary level. I wanted to explore the existing phenomena of the framing questions in the English classroom using phenomenological research design under a qualitative research approach in which 10 secondary-level English teachers from Kathmandu district, particularly Kirtipur municipality, were selected through a non-random purposive sampling procedure in this study. Higher-order thinking skills such as analyzing, evaluating, and creating are essential in developing the critical and creative thinking skills of learners at secondary level. The findings show fulfillment of objectives of the curricula, developing critical and creative thinking skills, developing positive thinking skills and motivation, and developing meta-cognitive and problem-solving skills through the use of the cognitive domain of Bloom Taxonomy. It is concluded that practices of framing questions based on the cognitive domain of Bloom Taxonomy are essential in enhancing the learning achievement of learners in English.